2022
DOI: 10.3390/info13020101
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Hemiplegia Type Detection (Right or Left) Using the Levenberg-Marquardt Backpropagation Method

Abstract: Hemiplegia affects a significant portion of the human population. It is a condition that causes motor impairment and severely reduces the patient’s quality of life. This paper presents an automatic system for identifying the hemiplegia type (right or left part of the body is affected). The proposed system utilizes the data taken from patients and healthy subjects using the accelerometer sensor from the RehaGait mobile gait analysis system. The collected data undergo a pre-processing procedure followed by a fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Based on previous research [12], [27]- [30] Following the finding that Levenberg-Marquardt backpropagation had the best accuracy result for gait detection, this present research used the same training algorithm. Fig.…”
Section: B Classification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research [12], [27]- [30] Following the finding that Levenberg-Marquardt backpropagation had the best accuracy result for gait detection, this present research used the same training algorithm. Fig.…”
Section: B Classification Resultsmentioning
confidence: 99%
“…Levenberg-Marquardt backpropagation was chosen as the training algorithm due to its better performance than another training algorithm [12]. Some studies found that Levenberg-Marquardt backpropagation has classification results above 95% [27]- [30]. EMG signals were classified into 8 classes, i.e., treadmill walking with speed 1, labeled as T1, treadmill walking with speed 2, labeled as T2, treadmill walking with speed 3, labeled as T3, treadmill walking with speed 4, labeled as T4, treadmill walking with speed 5 labeled as T5, ground walking labeled as GW, walked upstairs Labelled as UW and walked down stair labeled as DW.…”
Section: Classification Methodsmentioning
confidence: 99%
“…Then, a typical BP neural network [27,28], which usually has a two-layer feed-forward framework, sigmoid hidden neurons, and linear output neurons, is established, as shown in Figure 3. For the training process of the BP neural network, the dataset is split into training, validation, and testing sets in a ratio of 7:1.5:1.5, and the Levenberg-Marquardt algorithm is implemented [29,30]. The predicted spectrum coefficients of the BP neural network can be used to reconstruct the temperature field by substituting them into Equation (12).…”
Section: Establishment Of the Pod-bp Prediction Modelmentioning
confidence: 99%
“…Artificial neural network prediction has many algorithmic methods (i.e., Levenberg-Marquardt: LM, Bayesian regularization: BP, scaling conjugate gradient: SCG). The choice of algorithm depends on the extent of the data and the amount of data [40][41][42][43][44]. Jiaojiao F. (2018) [41] studied the estimated monthly mean daily global solar radiation using the neural network approach with the LM and BP algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The LM algorithm is widely used for predicting mathematical data, and can reduce the range between mathematical data. Therefore, the LM algorithm is appropriately used in this research [42].…”
Section: Introductionmentioning
confidence: 99%